A droplet digital PCR method for the detection of scale drop disease virus in yellowfin seabream (Acanthopagrus latus) - Yin, Bin; Mao, Can; Yu, Fangzhao; Li, Wangdong; Pan, Runhong; Feng, Wei; Li, Yong (Frontiers in Microbiology, 2024)
In this study, a ddPCR method for the detection of scale drop disease virus (SDDV) in yellowfin seabream (Acanthopagrus latus) was established based on Real-time fluorescence quantitative PCR detection methods and principles. The reaction conditions were optimized, and the sensitivity, specificity, accuracy, and reproducibility were assessed. The results showed that threshold line position was determined to be 1900 by the ddPCR method; the optimum annealing temperature for SDDV detection by the ddPCR method was 60℃; the limit of detection was 1.4-1.7 copies/μL; the results of specific detection of other common viruses, except for SDDV specific amplification, were all negative; and the relative standard deviation (RSD) for the reproducibility validation was 0.77%. The samples of yellowfin seabream (Acanthopagrus latus) liver, spleen, kidney, heart, intestine, brain, blood, muscle, skin and ascites with three replicates, respectively, were tested using the ddPCR method, and the results were consistent with clinical findings. The ddPCR method established in this study has the advantages of high sensitivity, high specificity, good reproducibility and simple steps for the quantitative detection of SDDV, which could be used for the nucleic acid detection of clinical SDDV samples, and provided a new quantitative method for the diagnosis of yellowfin seabream SDDV in the early stage of pathogenesis.